Pancasila Education Learning In Increasing National And State Awareness Among Students - Kusumawardana, Muhammad Yudha; Dewi Fitriani; Hilman, Cecep (ARRUS Journal of Social Sciences and Humanities, 2025)
Pancasila Education plays an important role in shaping national and state awareness among students. However, in reality, there are still students who do not understand and practice the values ​​of Pancasila in their daily lives. This study aims to analyze the learning of Pancasila Education to increase the awareness of nation and state of students at STKIP Bina Mutiara Sukabumi. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with students and lecturers, observations during the learning process, and documentation studies of academic materials and policies related to Pancasila Education. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that interactive Pancasila Education learning, discussion-based, and linking theory to social reality can increase students' awareness of the importance of national values. Students become more aware of the concepts of unity, tolerance, and responsibility as citizens. The findings of the study indicate that innovative and contextual learning contributes to strengthening the understanding and implementation of Pancasila values ​​among students.